The impact of orientation changes in kindergarten activity rooms in different light climate zones of China on indoor daylighting environment - Liuxiang Qi; Jianzhu Yang; Lei Gong; Wenyang Wu; Chong Wu (Scientific Reports)
Abstract Kindergarten activity rooms benefit children’s growth and development under good natural indoor lighting conditions. Therefore, it is of great significance to conduct research on the indoor daylighting effects of kindergarten activity rooms under different orientations. However, most of the existing studies are based on the analysis and simulation of fixed orientations and single elements, and lack of comprehensive evaluation and analysis. Based on the above problems, this study utilizes China’s light climate data and daylighting standards for kindergartens, and selects Linzhi, Kunming, Zhengzhou, Hangzhou, and Guiyang as the research locations, and comprehensively evaluates the indoor daylighting effects. The results of the study show that: (1) The daylighting effect of kindergarten activity rooms in China’s different light climate zones varies greatly, mainly affected by the daylighting orientation, and the high-quality daylighting orientations of the five cities mainly focuses on the range of 210°–255°; (2) The value of sDA of the five cities is basically more than 75%, the uniformity of daylighting effects has all achieved good or higher standards; (3) Guiyang is the least affected by glare, with the smallest impact time range, while the other four cities are more serious. This study explores the impact of sDA, illuminance, and DGP in kindergarten activity rooms on children. The results provide a valuable baseline and technical reference for the daylighting design of kindergarten activity rooms.